Perceived Importance of ICT in Preparing Early Childhood Education Teachers for the New Generation Children - Olowe Peter Kayode; KUTELU Bukola Olaronke (Institute of Advanced Engineering and Science, 2014)
Children of the present age are born into the world that is highly driven by Information and Communication Technology (ICT). They begin to manipulate ICT materials as soon as they grow old enough to manipulate things. There is need therefore to provide ICT-learning experiences that can aid their holistic development. To do this, early childhood professionals must be positive about the roles of ICT in children’s development. This study therefore investigated the perception of Early Childhood Education (ECE) lecturers and students on the importance of ICT in preparing ECE teachers for the new generation children. The study adopted the descriptive survey research design. 10 lecturers and 300 students of ECE were purposively selected as sample. One validated questionnaire titled “Questionnaire on Information and Communication Technology” (0.83) was used. Data collected was analysed using percentage, mean and standard deviation. Findings revealed that, using ICT in preparation of ECE teachers can help them to facilitate children’s cognitive, physical and social-emotional development, and as well sustain children’s interest in learning.Recommendations include training of all Nigerian ECE lecturers in the use of ICT for teaching and learning and equipment of departments of ECE in Nigerian Colleges of Education and Universities with adequate and relevant ICT materials.DOI: http://dx.doi.org/10.11591/ijere.v3i2.5405